REHABILITATION ROBOTS FOR ASSESSMENT AND DIAGNOSIS OF DISABILITIES - Saparova, Azhar (Nazarbayev University School of Engineering and Digital Sciences, 2024)
Lately, the use of robots in rehabilitation is widely accepted by clinics and therapists worldwide. Robots are being used for passive and active training to treat disabilities through physical therapy of patients with paralyzed or impaired movements due to strokes and other similar medical problems [1], [2]. However, due to number of problems such as lack quantifiable feedback, variance of training protocols and their efficacy between institutions and therapists[3], the observation of variation in biomechanical and bio signal parameters became vital. The main aim of the study is to use rehabilitation robots as a tool for two purposes, one of them being the treatment of disorders and disabilities, and the other being conducting pathophysiology and diagnosing the cause of disabilities. The main objective is to diagnosis Cerebral Palsy with the gait analysis and gait phase detection using Machine Learning algorithms.
Keywords: Type of access: Embargo